Development and validation of Australian aphasia rehabilitation best practice statements using the RAND/UCLA appropriateness method. Issue 7 (2nd July 2015) - Power, Emma; Thomas, Emma; Worrall, Linda; Rose, Miranda; Togher, Leanne; Nickels, Lyndsey; Hersh, Deborah; Godecke, Erin; O'Halloran, Robyn; Lamont, Sue; O'Connor, Claire; Clarke, Kim
Abstract : Objectives: To develop and validate a national set of best practice statements for use in post-stroke aphasia rehabilitation. Design: Literature review and statement validation using the RAND/UCLA Appropriateness Method (RAM). Participants: A national Community of Practice of over 250 speech pathologists, researchers, consumers and policymakers developed a framework consisting of eight areas of care in aphasia rehabilitation. This framework provided the structure for the development of a care pathway containing aphasia rehabilitation best practice statements. Nine speech pathologists with expertise in aphasia rehabilitation participated in two rounds of RAND/UCLA appropriateness ratings of the statements. Panellists consisted of researchers, service managers, clinicians and policymakers. Main outcome measures: Statements that achieved a high level of agreement and an overall median score of 7–9 on a nine-point scale were rated as 'appropriate'. Results: 74 best practice statements were extracted from the literature and rated across eight areas of care (eg, receiving the right referrals, providing intervention). At the end of Round 1, 71 of the 74 statements were rated as appropriate, no statements were rated as inappropriate, and three statements were rated as uncertain. All 74 statements were then rated again in the face-to-face second round. 16 statements were added through splitting existing items or adding new statements. Seven statements were deleted leaving 83 statements. Agreement was reached for 82 of the final 83 statements. Conclusions: This national set of 82 best practice statements across eight care areas for the rehabilitation of people with aphasia is the first to be validated by an expert panel. These statements form a crucial component of the Australian Aphasia Rehabilitation Pathway (AARP) (http://www.aphasiapathway.com.au ) and provide the basis for more consistent implementation of evidence-based practice in stroke rehabilitation.